Pengaruh Jenis Biomassa dalam Proses Karbonisasi terhadap Efisiensi Burner Tipe GT40 - Prayitno, Hadi; Dinata, Ragil Alvin; Amrul, Amrul; Kurniawan, Dondi; Nazarudin, Rizal; Saputra, Eko Wahyu (Politeknik Negeri Padang, 2024)
The use of biochar as an organic fertilizer has gained significant attention in the agricultural field. Biochar application can enhance soil fertility and promote agricultural sustainability. Converting agricultural waste into biochar can reduce dependency on chemical fertilizers. Incorporating biochar into the soil improves water retention and nutrient availability. This study aims to evaluate the effect of biomass types (bromelain and bamboo) during the carbonization process on burner efficiency in biochar production.The study utilized bromelain biomass, bamboo biomass, and a mixture of the two at a 50% bromelain and 50% bamboo ratio. The raw materials were carbonized using a rotary drum reactor. The reactor operated with heat supplied by a High-Speed Diesel (HSD)-fueled burner. The carbonizer reached a maximum temperature of 600°C. In addition to biochar, the carbonization process also produced syngas, which was subsequently used to substitute HSD as a fuel source.The results indicated that the type of biomass significantly influenced burner efficiency during the carbonization process. Biochar derived from bamboo tended to have a higher cellulose content, whereas biochar from bromelain exhibited greater thermal decomposition stability. This study provides new insights into the potential of utilizing bromelain and bamboo biochar as sustainable strategies for agricultural soil management.The research demonstrated that biomass type selection during carbonization had a substantial impact on burner efficiency, which ranged from 81.15% to 84.45%. The HSD consumption of the burner was recorded at 35.03 kJ/hour. The use of biochar as an organic fertilizer offers an environmentally friendly and sustainable solution. Converting agricultural waste into biochar can serve as a strategic agenda for agricultural waste management.